A Strategic Framework for Task Automation in Professional Services. (February 2021) - Sampson, Scott E.
Professional service jobs exist at the high end of the skill ladder; thus, some have assumed that highly trained professional workers are relatively immune to being replaced by automation. However, this assumption is a bit dubious because automation does not occur at the job level but rather at the task level, and some tasks within a professional job might be highly susceptible to automation disruption. This research builds on prior research by (1) empirically testing a model for automation of professional services and (2) developing a professional task-automation framework that shows how individual tasks within a given job can be enhanced or disrupted by automation in very different ways. Some tasks are augmented by automation and remain in the purview of professionally trained workers. Other tasks are deskilled by automation, allowing the tasks to be transferred to lower cost workers (who are aided by automation). Other tasks are moved directly to customers through self-service technologies, reducing or eliminating the need to interact with professionals or other workers. Finally, some professional tasks are centralized, which leverages professional workers' distinctive expertise. Our framework shows precipitating conditions for each task-automation strategy and outlines logic for reconfiguring tasks within professional service systems.